Identification of Pests and Natural Enemies of Mulberry Plants in Two Varieties at Rumah Sutera Alam Ciapus, West Java - Triandi, Adrian; Mubin, Nadzirum; Nurulalia, Lia (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2021)
Mulberry plant (Morus alba) is a plant that has social and economic importance. This plant development is often done to harvest the fruit and leaves. The social importance can be found in that this plant, especially in its leaves, is used in silkworm feed (Bombyx mori) and then silk is used in traditional clothes in Indonesia. Cultivation of mulberry plant (leaves and fruit) ideally by Integrated Pest Management (IPM) is necessary so that mulberry plants grow ideally and leaves have high quality and quantity without becoming a source of inoculum for pests and diseases of silkworm maintenance. Mulberry cultivation is generally carried out without using pesticide input so it is interesting in monitoring pests and natural enemies in the mulberry ecosystem. The research was conducted on two varieties of mulberry plants, namely Morus alba var. Kanva-2 and Morus cathayana in the same agroecosystem. Observation of pests and natural enemies was carried out using yellow sticky traps (YST) and pitfall traps (PFT). The orders and families found in the two varieties showed acroceridae family of 37.81% in the YST and hypogastruridae family with a value of 83.76% in the PFT observation.Keywords: IPM, Morus alba, natural enemies, pest, trapping.